UJI PREFERENSI KEONG MAS (Pomacea canaliculata L.) TERHADAP BEBERAPA TANAMAN - Agustina Etin Nahas; Rika Ludji; Angelina Ningsih Agung (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
This study aims to determine the preferences of the golden snail (Pomacea canaliculata L.). on several plants to determine alternative plants and host plants. This research was carried out in the Greenhouse of the Faculty of Agriculture, Nusa Cendana University, from March to May 2020. This study used a Completely Randomized Design (CRD) with four replicates and five treatments, so there were 20 experimental units. The treatments tested were plant types as feed: K1: mustard greens, K2: water spinach, K3: taro, K4: rice, and K5: water hyacinth. The initial weight of the feed was 50 g. The variables observed were the weight of the feed eaten every three days for two months and the development of the golden snail on each feed. The golden snail's development for each feed was observed in egg production, egg development, and longevity of the golden snail. Feed weight data were analyzed using variance followed by a 5% DMRT test. The golden snail's egg production, development, and longevity are presented in tables and described. The results showed that the feeding treatment of water spinach, mustard greens, taro, rice, and water hyacinth affected the eating preferences of the golden snail. Golden snail prefers to feed mustard greens than water spinach, taro, rice, and hyacinth. The golden snail produces eggs on water spinach and rice feed. The best golden snail reproduction was found on water spinach feed, which produces 1-3 groups of eggs, and the highest hatchability of golden snails was found on rice feed.